Jabatan Kerja Raya Daerah Kota Tinggi / Nur Shazreen A. Latif @ Suria - A.Latif @ Suria, Nur Shazreen (Faculty of Civil Engineering, 2018)
This report is set out to give the reader full information about my industrial training in Jabatan Kerja Raya Daerah Kota Tinggi in Johor. Industrial training is one of the compulsory curricular in Universiti Teknologi MARA which students need to complete it whether in private or government sector. This course is sets up for student in order to give them experience and gain knowledge in working environment before going through the real working life. My industrial training is in Jabatan Kerja Raya or known as JKR which functioning as a technical agency for Malaysia. JKR is responsible for implementing infrastructure development and maintenance projects to various ministries, departments, statutory bodies and state governments such as roads, buildings, airports, ports and jetty. During this industrial training, I have been assigned o work in Road Department from 8th July until 31 st July and 1 st August until 2nd September 2018 in Building Department. During my placement, I have gain a lot of new technical knowledge about road and building construction and its maintenance works. These knowledge is very useful for my future career. This report also includes the background of JKR, weekly summary of activities, technical report and the lessons learned while my industrial training.